Ocular complications of soft contact lens wearers in a tertiary eye care centre of Nepal - Sapkota, Kishor (2013)
Aim: To determine the prevalence and the major types of ocular complications related with soft contact lenses (CL) in a tertiary eye care centre of Nepal. Methods: Medical files of 4064 soft CL wearers who started wearing CL between January 2003 and December 2010 in BP Koirala Lions Centre for Ophthalmic Studies (BPKLCOS) Kathmandu, Nepal, were retrospectively reviewed. Records of patients who visited the hospital with complications were analyzed. Patients with ocular complications non-related with CL wear were excluded. Results: Complications were found in 4.9% of the total soft CL wearers. Contact lens induced papillary conjunctivitis (CLPC) was the most common complication, comprising 36.9% of the total patients with complications. The other commonly found complications were superior punctuate keratitis (SPK) in 16.2%, conjunctivitis in 18.2%, meibomian gland dysfunction (MGD) in 8.6%, contact lens induced peripheral ulcer (CLPU) in 4%, corneal vascularization in 3.5% and microbial keratitis in 3%. The average time of first occurrence of complications after starting of contact lens wear was 14.3 ± 11.4 months. Conclusion: CLPC, conjunctivitis and SPK were the most common types of soft CL related complications found in Nepal. Vision threatening complications like microbial keratitis was also found in some patients. Patient education in CL hygiene, after care schedule and frequent follow up examinations may help to minimize CL related complications.